2013
DOI: 10.1186/1472-6963-13-65
|View full text |Cite
|
Sign up to set email alerts
|

“I feel it is not enough…” Health providers’ perspectives on services for victims of intimate partner violence in Malaysia

Abstract: BackgroundThis study explores the views and attitudes of health providers in Malaysia towards intimate partner violence (IPV) and abused women and considers whether and how their views affect the provision or quality of services. The impact of provider attitudes on the provision of services for women experiencing violence is particularly important to understand since there is a need to ensure that these women are not re-victimised by the health sector, but are treated sensitively.MethodsIn-depth interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 33 publications
(37 reference statements)
3
57
0
3
Order By: Relevance
“…A relevant finding of this study is the high percentage of undergraduate nurses training programmes that have included GBV in their curricula, showing a very positive change to previous research findings in the country, where none of the autonomous regions had institutionalized training in GBV (Goicolea et al, 2013). At international level, although no similar studies that allow for comparison have been found, the repeated call for specific training in the topic in many publications (Colombini et al, 2013;Damra et al, 2015;WHO, 2013b), reflect that institutionalized training in GBV is scarce. Therefore, the extensive inclusion of GBV training found in this research might be the first step for a turning point in the health-care sector response to GBV in Spain.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A relevant finding of this study is the high percentage of undergraduate nurses training programmes that have included GBV in their curricula, showing a very positive change to previous research findings in the country, where none of the autonomous regions had institutionalized training in GBV (Goicolea et al, 2013). At international level, although no similar studies that allow for comparison have been found, the repeated call for specific training in the topic in many publications (Colombini et al, 2013;Damra et al, 2015;WHO, 2013b), reflect that institutionalized training in GBV is scarce. Therefore, the extensive inclusion of GBV training found in this research might be the first step for a turning point in the health-care sector response to GBV in Spain.…”
Section: Discussionsupporting
confidence: 48%
“…Evidence shows that training can increase knowledge, improve self-efficacy and help health-care professionals acquire skills to successfully respond to women exposed to GBV (Connor et al, 2013;Murillo et al, 2017). Consequently, the inclusion of training in GBV for both undergraduate students and health-care professionals has been strongly recommended in international literature (Colombini et al, 2013(Colombini et al, , 2012Damra et al, 2015;WHO, 2013b). In Spain, where this study took place, these recommendations have also been reflected in legislation.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Se ha señalado que las definiciones de la VCM están influidas por normas culturales, experiencias personales y emociones (36). Como personas que viven en una sociedad estructurada por el sistema de género entre otros ejes de desigualdad social, los y las profesionales sanitarios han sido socializados con los mismos valores culturales y en similares niveles de violencia que los y las usuarios que acuden a sus centros de salud (37) (38). En consecuencia es lógico que sus definiciones sobre la VCM reflejen opiniones machistas internalizadas (12) (36).…”
Section: Discussionunclassified
“…En consecuencia es lógico que sus definiciones sobre la VCM reflejen opiniones machistas internalizadas (12) (36). Colombini y colegas (38) señalan que existe una relación entre cómo los y las efectores de salud conciben la VCM y su respuesta frente a la problemática. Por tanto es crucial fortalecer el conocimiento sobre la VCM desde una perspectiva de género y de derechos humanos para garantizar el correcto abordaje de la VCM.…”
Section: Discussionunclassified
“…A study conducted with 54 health professionals who provide care to women victims of intimate partner violence in two states and in the north of Malaysia state that these women should be treated with sensitivity by health services, and which should seek care strategies without re-victimizing them (16) . Institutional conditions to prioritize their attendance should be created.…”
Section: Discussionmentioning
confidence: 99%